Growth and Yield of Indoor-Cultivated Mustard Microgreens against the Duration of LED Irradiation and Variations in Planting Media - Tri Putri Nur; Nuni Gofar (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
The limitations of agricultural land currently encourage cultivation activities to be carried out with the use of limited space such as indoor cultivation by utilizing irradiation techniques and the use of varied planting media. This study aimed to evaluate the  growth and yield of  indoor-cultivated mustard microgreens to the irradiation duration and the composition of varied planting media. This study used a split plot design with the treatment of LED irradiation duration of 0, 10, and 20 hours/day, and the variations  of planting media, 100% soil, 100% compost, addition of 50% compost and cocopeat, and a combination of compost and cocopeat planting. The study results showed that the irradiation only affected the plant height in the both planting periods. The treatment of the composition of the planting media had significant effect on all variables observed in the two planting periods, while the interaction had a very significant effect on the plant height on 1st planting period and root length on 2nd planting period. The treatment of 50% soil + 50% compost on LED 10 hours/day had the highest yield of fresh weight in two planting periods. The use of 100% soil media inhibited the growth of mustard microgreens, while the irradiation of 0 hours/day in all planting media treatments showed the symptoms of etioliation. So, the treatment of 10 hours/day irradiation with the addition of 50% compost is able to provide  the best results in quality and quantity against the pH value and the growth and yield of mustard  microgreens.